High power free electron maser based on a two-dimensional bragg cavity - Konoplev, I; McGrane, P; Cross, A; Phelps, A; He, W; Whyte, C; Ronald, K; Ginzburg, N; Peskov, N; Sergeev, A; Thumm, M (2004)
The use of two-dimensional (2D) Bragg structures has been suggested for application in microwave electronics and integrated optics to synchronise radiation from different parts of an oversized active medium and to improve mode selection inside the interaction space. Computational modelling and experimental measurements of the field evolution inside co-axial 2D Bragg structures as well as recent progress in the use of these structures to define the cavity of a high power Free Electron Maser will be presented. The 2D Bragg cavity has been designed and constructed. Microwave measurements have been performed using a Vector Network Analyser. Good agreement between the measured transmission properties of the 2D Bragg structures and PIC code (MAGIC) simulations was obtained. The high current accelerator to drive the FEM consists of a Marx bank power supply which resonantly charges a transmission line which sub-sequently discharges through a high pressure (16Bar) nitrogen-filled spark gap providing a 200ns duration flat-top high voltage pulse to an explosive emission electron (EEE) gun diode immersed in a 0.6T guide field provided by a 30cm diameter 2.25m long solenoid. The guide magnetic field insulates and confines an annular relativistic electron beam of energy 500keV. The oversized (7 cm diameter) annular electron beam was passed through an azimuthally symmetric wiggler with the interaction space defined by two-dimensional (2D) Bragg structures. The maximum possible beam current transportable through the diode region and interaction space was calculated using the 2.5D PIC code KARAT. An electron beam of power 750MW has been measured in the experiment. An FEM output efficiency of up to 15% has been predicted by the calculations. This paper will present the progress made towards the generation of ∼100MW of power from the co-axial 2D Bragg FEM operating at a frequency of 37.5GHz.